Assessment of geomorphological and hydrological changes produced by Pleistocene glaciations in a Patagonian basin. (April 2018) - Scordo, Facundo; Seitz, Carina; Melo, Walter D.; Piccolo, M.Cintia; Perillo, Gerardo M.E.
Abstract: This work aims to assess how Pleistocene glaciations modeled the landscape in the upper Senguer River basin and its relationship to current watershed features (drainage surface and fluvial hydrological regime). During the Pleistocene six glacial lobes developed in the upper basin of the Senguer River localized east of the Andean range in southern Argentinean Patagonia between 43° 36' - 46° 27′ S. To describe the topography and hydrology, map the geomorphology, and propose an evolution of the study area during the Pleistocene we employed multitemporal Landsat images, national geological sheets and a mosaic of the digital elevation model (Shuttle Radar Topography Mission) along with fieldwork. The main conclusion is that until the Middle Pleistocene, the drainage divide of the Senguer River basin was located to the west of its current limits and its rivers drained the meltwater of the glaciers during interglacial periods. However, processes of drainage inversion and drainage surface reduction occurred in the headwater of most rivers of the basin during the Late Pleistocene. Those processes were favored by a relative shorter glacial extension during LGM and the dam effect produced by the moraines of the Post GPG I and III glaciations. Thus, since the Late Pleistocene, the headwaters of several rivers in the basin have been reduced, and the moraines corresponding to the Middle Pleistocene glaciations currently divide the watersheds that drain towards the Senguer River from those that flow west towards the Pacific Ocean. Highlights: Pleistocene glaciations modeled Senguer River basin landscape in Argentinian Patagonia. During the Pleistocene six ice lobes developed in Senguer River upper basin. The basin boundary was located west of its current limits until Middle Pleistocene. During Last Glacial Maximum, the basin drainage inverted and its surface reduced. Most of the basin rivers are now intermittent.